Operation Neptune Spear and the Manhunt (Implications for Pakistan United States Counter Terrorism Synergism 2001-2020) - Dr. Muhammad Iqbal Roy; Abubaqar Khalid; Abdul Rehman; Farhan Khalid (Journal of Political Studies, 2022)
The qualitative, descriptive & analytical study emphasis on the US military operation against Osama Bin laden the founder of Al-Qaeda, who was killed on May 1, 2011 in Bilal town compound Abbottabad Pakistan, which was purchased by Abu Ahmad Al-Kuwaiti of 50,000 during 2004-5. The former US president Bill Clinton had announced to arrest Bin Laden either live or dead in 1992. Clinton claimed that “the historic record of America does not confirm that it had even left off its foes. How the US administration stipulated a sum of 250 million for various military & intelligence operations to persuade Osama Bin Laden since the US started war on terror against Al-Qaida & its associates as the major culprits of the devastating events of 9/11? The Clinton’s proclamation of killing Osama Bin Laden was practically executed during Obama’s regime on May 1, 2011.The US intelligence & security agencies used Black Hawks, Navy Seals including 79 Commandos and a dog called Cairo. The Operation Neptune Spear imprinted multi-faceted implications on Pakistan’s Socio-Political and economic environment and put its credibility at the stake of trust deficit in the context of Pakistan-United States working relationship fighting against terrorism during 2001-2020. The study examines how Pakistan had to face a severe internal and external criticism and cost along with a serious retaliation of the terrorist activities i.e. suicidal attacks in the post Abbottabad operation scenario?